Massive gastrointestinal haemorrhage caused by pancreatic pseudocyst complicated with Dieulafoy's disease in a child: A case report and review of the literature - Liu, Lintao; Zhang, Lichao; Zhu, Xiaoli; Li, Meng; Cao, Juan; Ji, Likang; Qi, Xiaoyang; Xu, Weili (Frontiers in Pediatrics, 2022)
Abstract Background: Pancreatic pseudocyst (PPC) with massive gastrointestinal bleeding are rare, especially in children. Inadvertent intraoperative examination and damage to the gastric mucosa and malformed blood vessels by the fluid content of PPC can lead to massive bleeding, which may endanger the patient's life. Case Presentation: Here, we present a case of an 8-year-old boy who was diagnosed with massive gastrointestinal haemorrhage caused by PPC complicated with Dieulafoy’s disease. At the first admission, his complain was being hit to the stomach by the handlebar while riding bicycle 24 hours before admission. After being hospitalized, he was diagnosed with pancreatic injury by abdominal CT. Conservative treatment lasted for one month in the Department of Paediatric Surgery. Then, a pancreatic pseudocyst formed. Under the guidance of ultrasonic endoscopy, cyst puncture and drainage of pseudocysts through the gastric wall were performed. Unexplained haematemesis occurred eight days after surgery. Emergency gastroscopy was performed, and abnormal submucosal vascular haemorrhage was found at the gastric fundus. Gastric Dieulafoy’s disease was diagnosed. The boy underwent gastroscopic titanium clipping of abnormal arteries. He had no complications during the 3-month follow-up. Then, the patient returned to the hospital, and the stent was removed under endoscopy. No bleeding was found, and the patient was discharged. The patient recovered smoothly and was followed up for half a year without any complications, and haematological indicators were normal. Conclusion: Endoscopic ultrasonography-guided gastric puncture and internal drainage of cysts is a safe and effective surgical method for the treatment of pancreatic pseudocysts. However, at the same time, it is necessary to thoroughly and carefully explore the stomach cavity to prevent adverse consequences caused by missed diagnosis of gastric Dieulafoy’s disease or other abnormal abnormalities.